Letter to JSU President Houston Cole from Johnnie E. Mackin, August 1969 - Mackin, Johnnie E. (JSU Digital Commons, 1969)
Letter to JSU President Houston Cole from Johnnie E. Mackin, Contracting Officer at Fort McPherson, GA regarding renegotiation of all contracts for training ROTC cadets under the Financial Assistance Program. Enclosed is an educational service agreement, August 20, 1969. https://digitalcommons.jsu.edu/rotc_docs/1017/thumbnail.jpg